2020
DOI: 10.12659/msm.920442
|View full text |Cite
|
Sign up to set email alerts
|

Notoginsenoside R1 Suppresses Inflammatory Signaling and Rescue Renal Ischemia-reperfusion Injury in Experimental Rats

Abstract: Departmental sources Background:Notoginsenoside R1 (NR) is a major dynamic constituent of Panax notoginseng found to possess anti-inflammatory activity against various inflammatory diseases. However, its protective effects against renal ischemiareperfusion (I/R) injury have not been elucidated. In male Wistar rats, we induced I/R under general anesthesia by occluding the renal artery for 60 min, followed by reperfusion and right nephrectomy. Material/Methods:Rats were randomized to 4 groups: a sham group, an I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…PNS imparted protective roles against human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) and DSS-induced colitis via regulating the levels of caspase-3, 8, 9, and PI3K/AKT signaling pathway respectively [ [284] , [285] ]. Further, Notoginsenoside R1 (NR), isolated from Panax notoginseng , imparted protective effects against the rat model of renal ischemia-reperfusion (I/R) injury via downregulation of certain oxidative and inflammatory factors such as TNF-α, TGF-ß1, IFN-γ, and IL-6 [ 286 ]. Ginsenoside Rg3 (GRg3) induces anti-inflammatory effects and ameliorates RA in vivo via the CD4 + CD25 + Foxp3 + Treg cells [ 287 ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%
“…PNS imparted protective roles against human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) and DSS-induced colitis via regulating the levels of caspase-3, 8, 9, and PI3K/AKT signaling pathway respectively [ [284] , [285] ]. Further, Notoginsenoside R1 (NR), isolated from Panax notoginseng , imparted protective effects against the rat model of renal ischemia-reperfusion (I/R) injury via downregulation of certain oxidative and inflammatory factors such as TNF-α, TGF-ß1, IFN-γ, and IL-6 [ 286 ]. Ginsenoside Rg3 (GRg3) induces anti-inflammatory effects and ameliorates RA in vivo via the CD4 + CD25 + Foxp3 + Treg cells [ 287 ].…”
Section: Anti-inflammatory Role Of Spicesmentioning
confidence: 99%
“…In animal studies, NGR1 has been proven to have various effective therapeutic functions, such as neuroprotection, anti‐diabetes, certain organ protection, bone metabolism regulation, anti‐cancer and osteoporosis, which can be largely attributed to its potent antiapoptotic, anti‐inflammatory and anti‐oxidative properties 13,51 . NGR1 has been shown to effectively protect various types of cells from oxidative damages triggered by other pathological factors, such as AGEs (advanced glycation end products), 16 ischaemia‐reperfusion injury 52 and oxidized low‐density lipoprotein 53 . NGR1 can decrease ROS production and prevent protein and lipid peroxidation by improving the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase and glutathione 15,52,54 .…”
Section: Discussionmentioning
confidence: 99%
“…NGR1 has been shown to effectively protect various types of cells from oxidative damages triggered by other pathological factors, such as AGEs (advanced glycation end products), 16 ischaemia‐reperfusion injury 52 and oxidized low‐density lipoprotein 53 . NGR1 can decrease ROS production and prevent protein and lipid peroxidation by improving the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase and glutathione 15,52,54 . As expected, our current study also showed that NGR1 antagonized the H 2 O 2 ‐induced OS, restored cell viability and decreased apoptosis rate of osteoblast (Figure 1A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Panax notoginseng (Burkill) F.H.Chen and panax notoginseng saponins could protect kidney from diabetes via the mechanism of upregulating SIRT1, therefore activating antioxidant proteins and inhibiting inflammation by decreasing the inflammatory cytokines ( Du et al, 2016 ). Notoginsenoside R1 is a promising drug for the prevention and treatment of renal insufficiency through inhibition of the production of inflammatory cytokines induced by ischemic reperfusion and inhibition of oxidative stress ( Fan et al, 2020 ). In vitro , notoginsenoside R1 protects human renal proximal tubular epithelial cells from lipopolysaccharide (LPS)-induced inflammatory injury by upregulating miR-26a and inactivating the NF-κB pathway ( Liu et al, 2019b ).…”
Section: Mechanisms Of Chinese Herbal Medicines In Treating Kidney DImentioning
confidence: 99%